2007
DOI: 10.1371/journal.pone.0001055
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Gene Transfer Regulation in Bacteria as a “Spandrel” of DNA Repair Mechanisms

Abstract: Horizontal gene transfer (HGT) is recognized as the major force for bacterial genome evolution. Yet, numerous questions remain about the transferred genes, their function, quantity and frequency. The extent to which genetic transformation by exogenous DNA has occurred over evolutionary time was initially addressed by an in silico approach using the complete genome sequence of the Ralstonia solanacearum GMI1000 strain. Methods based on phylogenetic reconstruction of prokaryote homologous genes families detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 51 publications
4
47
0
Order By: Relevance
“…However, some lines of evidence in this study, and several other studies (Bertolla et al, 1999;Fall et al, 2007;Guidot et al, 2009;Coupat-Goutaland et al, 2011), suggest an important contribution of recombination and horizontal gene transfer in the evolutionary dynamics of R. solanacearum.…”
Section: Introductionsupporting
confidence: 45%
“…However, some lines of evidence in this study, and several other studies (Bertolla et al, 1999;Fall et al, 2007;Guidot et al, 2009;Coupat-Goutaland et al, 2011), suggest an important contribution of recombination and horizontal gene transfer in the evolutionary dynamics of R. solanacearum.…”
Section: Introductionsupporting
confidence: 45%
“…Differences in recombination frequencies based on genomic positions was previously reported in Ralstonia solanacearum (Fall et al 2007), with positions containing recombination hot spots (recA and mutS) showing the highest frequency (Fall et al 2007). In this study, higher recombination frequency was observed for pKLN61, a plasmid that recombines in the region of rpfF gene, a diffusible signaling factor involved in cell-to-cell communication of X. fastidiosa (Newman et al 2004), compared with pAX1.Cm, which recombines at a neutral site (Matsumoto et al 2009), and pMOPB-Km and pMSRA-Km, which recombine at regions whose functions are being characterized.…”
Section: Discussionmentioning
confidence: 65%
“…This is to be expected even if the benefits are large and common. Homologous recombination typically falls off rapidly with genetic distance (19), so a well-established population will usually reflect the mixing of relatively similar alleles. This mixing can be easily detected by the lack of clonality between genes and quantified using evolutionary models (e.g., ClonalFrame) (20); however, detection of recombination breaks within genes is more problematic.…”
mentioning
confidence: 99%